Pengaruh Era Teknologi di Bidang Pendidikan Pada Yayasan Yatim Piatu Hidayatullah - Iqbal, Moehammad (Jurnal Kreativitas Mahasiswa Informatika, 2021)
The purpose of this Community Service activity is to share knowledge with the children of the Hidayatullah Orphanage in the Pondok Lightning Village, Bojong Sari - Depok, West Java. The participants who attended were 20 people. This activity is a form of sharing knowledge about how the influence of the technological era in the field of education. The presentation of the material is carried out through presentations through the facilities provided in the form of monitors to participants so that the information obtained is clearer and more complete. The material presented is also in the form of questions and answers so that the activities run interactively. And this activity was carried out by implementing the 3M health protocol due to the current situation of the Covid-19 virus pandemic. Keyword : Technology,Covid-19, Education